Penerapan Strategi Digital Marketing Melalui Platform Media Sosial Facebook Ads - Luthfiah Nur Fatikha; Mohamad Maftuh Fauzi (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
Currently, technological developments in Indonesia are occurring very rapidly, which has resulted in increasingly sophisticated facilities. One form of technology integration is in marketing practices using digital marketing strategies. The aim of this research is to conceptually examine digital marketing strategies through the Facebook Ads platform to increase competitiveness in the market. The type of research is a descriptive qualitative approach. Research data is primary and secondary data in the form of information from supervisors and team members, as well as theory and empirical findings from previous research obtained using literature studies. The conclusion that can be drawn from the results of the discussion states that digital marketing strategy is a form of marketing that emphasizes brand communication to be able to strengthen its competitiveness in the digital market and increase income significantly. Theoretically, digital marketing strategies through the social media platform Facebook Ads can not only influence brand satisfaction, but can also lead to increased brand trust and brand loyalty.